2018
DOI: 10.1159/000492133
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies and Characteristics of Choroidal Neovascularization in Young Chinese Patients

Abstract: Purpose: To investigate the etiologies and characteristics of choroidal neovascularization (CNV) in young Chinese patients. Methods: A retrospective review of young Chinese patients (< 50 years of age) with CNV from January 2010 to June 2016 was performed. Results: Of the 501 patients (537 eyes) with CNV, 58.7% were female, and 7.2% had bilateral CNV. The mean age was 35 years. The etiologies were idiopathic CNV (ICNV, 43.9%), pathologic myopia (PM, 21.9%), punctate inner choroidopathy (PIC, 17.4%), polypoidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…CNV is a pathological change that occurs in a variety of retinal and choroidal diseases and seriously affects patients' vision and reduces their quality of life [10]. Previous research has found that the most common aetiologies of CNV among young patients are pathologic myopia, inflammation, and ICNV [10,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CNV is a pathological change that occurs in a variety of retinal and choroidal diseases and seriously affects patients' vision and reduces their quality of life [10]. Previous research has found that the most common aetiologies of CNV among young patients are pathologic myopia, inflammation, and ICNV [10,20].…”
Section: Discussionmentioning
confidence: 99%
“…CNV is a pathological change that occurs in a variety of retinal and choroidal diseases and seriously affects patients' vision and reduces their quality of life [10]. Previous research has found that the most common aetiologies of CNV among young patients are pathologic myopia, inflammation, and ICNV [10,20]. Usually, CNV secondary to MFC can be differentiated from mCNV lesions by the presence of vitreous cells and via fundus examination according to the characteristic yellow-white or punched-out lesions that present with early hyperfluorescence and late fluorescence leakage in FFA in the same or the fellow eye [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several treatment methods have been introduced for pediatric CNV [8][9][10], but the recent therapeutic paradigm is shifting toward the use of anti-vascular endothelial growth factor (VEGF) [11]. Several studies have reported the usefulness of anti-VEGF in pediatric CNV, but most are retrospective case series reports [2,4,6,7,11,12], and studies in Asian patients are few [6,13]. Recently, a study on pediatric CNV patients using a large database was reported [14].…”
Section: Introductionmentioning
confidence: 99%